ANALISIS PERBEDAAN HARGA SAHAM, VOLUME PERDAGANGAN SAHAM DAN RETURN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT - lailatus saadah; Achmad Ferrizky Affan; Mohammad Soedarman (Prodi Akuntansi FEB UNITOMO, 2023)
This study aims to compare stock prices, stock trading volume and stock returns before and after a stock split. This study uses quantitative secondary data and uses a test conducted by Wilvoxon Signed Ranks. The population used in this study are companies that have carried out stock splits released by the Indonesia Stock Exchange (IDX) in 2019-2021. The sampling technique of this study was purposive sampling and based on predetermined criteria, 27 companies were obtained as samples. In this study, the paired sample t-test was used to analyze stock prices, trading volume and stock returns before and after a stock split. Based on the results of the data analysis that has been examined, the following conclusions are drawn (1) the stock price before and after the stock split, namely Sig.2 tailed) 0.829 exceeds the significance level of 0.05 so it can be concluded that the stock split does not have an effect on stock prices, (2) the average volume of stock trading before the stock split and also after the stock split has different results if a different test is carried out using the program from SPSS 25 and the Wilcoxon test. The fact that 2-tailed) is significantly higher than the 0.05 level of 0.461 indicates that the stock split has no effect on stock trading volume (3) the average stock return after and before the stock split is far below the significance level, namely 0.0 5 so it can be concluded that the stock split has an impact on stock returns.